Self-Benefit versus Other-Benefit Marketing Appeals: Their Effectiveness in Generating Charitable Support - White, Katherine; Peloza, John (Journal of Marketing, 2009)
Despite the growing need, nonprofit organization marketers have not yet fully delineated the most effective ways to position charitable appeals. Across five experiments, the authors test the prediction that other-benefit (self-benefit) appeals generate more favorable donation support than self-benefit (other-benefit) appeals in situations that heighten (versus minimize) public self-image concerns. Public accountability, a manipulation of public self-awareness, and individual differences in public self-consciousness all moderate the effect of appeal type on donor support. In particular, self-benefit appeals are more effective when consumers’ responses are private in nature; in contrast, other-benefit appeals are more effective when consumers are publicly accountable for their responses. This effect is moderated by norm salience and is related to a desire to manage impressions by behaving in a manner consistent with normative expectations. The results have important managerial implications, suggesting that rather than simply relying on one type of marketing appeal across situations, marketers should tailor their marketing message to the situation or differentially activate public self-image concerns to match the appeal type.